Career development and human resource management of older workers: A scoping review. (October 2021) - Mok, Irene; Mackenzie, Lynette; Thomson, Kate
Career development for older workers is an emerging challenge to human resource management (HRM) which aims to improve the employability of older workers and mitigate labour and skill shortage problems. This review synthesised findings from 15 studies referring to career development and HRM practices for older workers. The aims were to examine the definition of career development for older workers and factors that affect the provision of career development. The five-step scoping review process outlined by Arksey and O'Malley (2005) was followed. Results indicated that when career development is incorporated as a part of HRM practices it improved employability and retention of older workers. However, the lack of definitional clarity of what career development meant for an ageing workforce made it challenging for organisations to integrate it into their HRM practices. Further research is needed to examine implementation barriers and find ways to increase collaboration between older workers and organisations.